A new Ctenothrips from southwestern China (Thysanoptera: Thripidae) - Xie, Yonghui; Zhang, Hongrui; Li, Zhengyue (Zootaxa, 2011)
The genus Ctenothrips (Thysanoptera, Thripidae) was proposed by Franklin in 1907 with C. bridwelli as the type species from North America (Franklin, 1907). Up to now, eleven species have been known, all from the Holarctic region (Mound, 2011; Haga & Okajima, 1989; Kudo, 1977; Bhatti, 1976), and six of these have been described from China (Chen, 1979; Feng et al., 2003; Tong & Zhang, 1992). Though related to one of the most popular genera, Taeniothrips Amyot and Serville, by having similar head and antennae, Ctenothrips is distinctly characterized with polygonally reticulated body surface of abdomen and tube-like abdominal segment X. Species of the genus Ctenothrips have been found mainly in alpine regions, but we collected the new species described here from an area only as high as altitude of 900m in the southwest of China. In this paper, C. guizhouensis sp. n., is added as the twelfth member to this genus, and an identification key is provided to all 12 species, based mainly on descriptions. The new species was collected in the flowers of a species of Galium (Rubiaceae) at the Donggong temple, Zunyi City, Guizhou Province. The type specimens are preserved in Yunnan Agricultural University.